2019
DOI: 10.1007/s10570-019-02754-w
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of cellulose nanofibers from aspen wood using derivatizing and non-derivatizing pretreatments

Abstract: The link between wood and corresponding cellulose nanofiber (CNF) behavior is complex owing the multiple chemical pretreatments required for successful preparation. In this study we apply a few pretreatments on aspen wood and compare the final CNF behavior in order to rationalize quantitative studies of CNFs derived from aspen wood with variable properties. This is relevant for efforts to improve the properties of woody biomass through tree breeding. Three different types of pretreatments were applied prior to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 55 publications
4
34
1
Order By: Relevance
“…The mechanical properties of the nanofibril network from the mechanically treated CNFs (NW-M) are lower than those of the chemically-mechanically treated (NW-CM) and chemically treated (NW-C) networks. A similar phenomenon has been observed previously (Jonasson et al 2020) and indicates the importance of pretreatment before homogenization to obtain enhanced network properties. Enhanced toughness, which was observed in the TW CNF networks, has also been observed for nanofibril networks of high-DP CNFs, both experimentally (Henriksson et al 2008;Fukuzumi et al 2013) and theoretically (Meng et al 2017).…”
Section: X-ray Diffractionsupporting
confidence: 88%
“…The mechanical properties of the nanofibril network from the mechanically treated CNFs (NW-M) are lower than those of the chemically-mechanically treated (NW-CM) and chemically treated (NW-C) networks. A similar phenomenon has been observed previously (Jonasson et al 2020) and indicates the importance of pretreatment before homogenization to obtain enhanced network properties. Enhanced toughness, which was observed in the TW CNF networks, has also been observed for nanofibril networks of high-DP CNFs, both experimentally (Henriksson et al 2008;Fukuzumi et al 2013) and theoretically (Meng et al 2017).…”
Section: X-ray Diffractionsupporting
confidence: 88%
“…In addition, previous results with CCIMI (treatment time of 4 h at 100°C) showed a significantly lower tensile strength compared to the current study ( Table 2, entry 3). 25 It should be noted that in Table 2, the mechanical properties of films with randomly oriented nanofibers are reported. Orientation-for example, by drawing-can significantly improve the mechanical properties of the films.…”
Section: Mechanical Properties Of Cnf Filmsmentioning
confidence: 99%
“…19,20 Nonmodifying methods (i.e., no or only minimal decrease in DP or alteration of cellulose structure) based on deep eutectic solvents (DESs) have recently been used for the sustainable production of CNFs. [21][22][23][24][25] In addition to DESs' use as nonmodifying pretreatment media, they can be harnessed as solvents for chemical derivatization 26,27 and as reagents 28 that can even be recycled 29 in CNF production. DESs are ionic liquid analogues that are obtained by the simple mixture of two or more components and can often be derived from green and bulk chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment has been studied in great depth in relation to delignified pulps from a variety of sources [ 6 ]. It has also been demonstrated that feedstock containing lignin, such as thermomechanical pulp [ 7 ], hemp [ 8 ] and wood [ 9 ], can be simultaneously delignified and carboxylated using the treatment. The relation between these procedures and nanofibrillation is complex where CNFs with residual lignin are attainable despite substantial carboxylation [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The associated novelty includes highlighting TEMPO-oxidation as a metric of fibrillation suitability for raw wood with variation in lignin content, something which could be applicable to commercial endeavors where TEMPO-oxidation is an attractive prospect in obtaining CNFs. Direct TEMPO-oxidation of wood has only recently been the subject of few dedicated studies [ 9 , 13 ]. These studies were furthermore showcasing one type of wood whereas the study presented herein aims to explore an additional factor of wood characteristics.…”
Section: Introductionmentioning
confidence: 99%